Literature of Review Influence Word Of Mouth, Satisfaction and Brand Image of Purchases Mandiri Jaya Frozen in Bekasi - Dewi Puspaningtyas Faeni; Riki Nur Allpiah (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This study reviews the literature to determine how purchase decisions are influenced by word-of-mouth, satisfaction, and brand image. The frozen enterprises in Bekasi City are the subject of this study. The relationship between the independent and dependent variables will be made clear by this study. This study employs a quantitative design with samples derived from the Slovin technique and a consumer population from Frozen Duck Queen. To process research data and address research hypotheses, this study will make use of statistical techniques from SPSS.